Photothermal Synergistic Hydrogen Production via a Fly‐Ash‐made Interfacial Vaporific System - Yin Xie; Chenyu Xu; Yan Liu; Entao Zhang; Ziying Chen; Xiaopeng Zhan; Guangyu Deng; Yuan Gao; Yanwei Zhang (Advanced Science)
Abstract Employing UV–vis spectrum for hydrogen generation and vis‐IR spectrum to elevate reaction temperatures and induce phase transitions effectively enhances yield and purifies water, demonstrating a judicious strategy for solar energy utilization. This study presents an interfacial photothermal water splitting system that utilizes all‐inorganic, economical industrial by‐products known as fly ash cenospheres (FAC) for solar‐driven hydrogen generation. In this system, the yield reaches 254.8 µmol h−1 cm−1, representing an 89% augmentation compared to that of the three‐phase system. In situ experiments, combined with theoretical calculation, reveal the system's robust light absorption capacity, facilitating rapid gas separation, thus improves the solar‐to‐hydrogen (STH) efficiency. Furthermore, the system demonstrates strong performance in turbid water and scalability for expansive applications, achieving a hydrogen yield exceeding 50 L h−1 m−2 from various water sources. Facilitating large‐scale hydrogen production and water purification, it thereby establishing its potential as a viable solution for sustainable energy generation.